Design Of A Gamified Financial Application Interface To Enhance Generation Z Engagement Using User-Centered Design - Muhammad Zakie Irdana; Irving Vitra Paputungan (Jurnal Media Computer Science, 2026)
The low level of Generation Z engagement in personal financial management has become a challenge in the use of digital financial applications. Although Generation Z is highly familiar with technology, many still lack the habit of recording expenses, managing budgets, and monitoring their financial condition consistently. This study aims to design a web-based financial management application interface by integrating gamification elements to increase user engagement. The method used is User-Centered Design (UCD), which involves identifying user needs, designing the interface, developing prototypes, and evaluating the system. The design results produced several main features, including transaction recording, budget management, financial goals, and activity history. In addition, the system is equipped with gamification elements such as progress bars, streaks, badges, and rewards to improve user motivation. Functional testing showed that all system features operated according to user requirements. Usability evaluation using the System Usability Scale (SUS) resulted in an average score of 79.9, which falls into the good and acceptable category. The analysis results indicate that the implementation of gamification can improve user motivation and engagement through progress visualization, immediate feedback, and habit formation through repeated activities. Therefore, the integration of gamification into the interface design of a web-based financial management application has proven effective in improving user experience and supporting the consistency of Generation Z in managing personal finances.